IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY BERDASARKAN KONSEP TRI HITA KARANA PADA HOTEL BALI TROPIC NUSA DUA - Pandita Budi, Putu Raynatha Ugra; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.01.TAHUN.2024, 2024)
Corporate Social Responsibility (CSR) is the concept of a business run by an institution/company as an obligation to stakeholders and the surrounding environment. This study aims to determine the implementation of CSR based on the Tri Hita Karana concept at the Bali Tropic Nusa Dua Hotel. This study uses a descriptive qualitative approach, where the technique of determining the sample uses several criteria. Collecting data using interviews, observation, and documentation. To gather more comprehensive and in-depth information from the informant's perspective, the ethnographic method was employed. The results show that CSR practices based on the Tri Hita Karana concept have been carried out in accordance with the THK philosophy which causes the level of trust of the surrounding community to increase, and also increases inequality and welfare for the people who receive assistance around the Bali Tropic Hotel.